1979
DOI: 10.1002/art.1780220209
|View full text |Cite
|
Sign up to set email alerts
|

Joint effusions after kidney transplantation

Abstract: Thirty-seven consecutive renal transplant recipients were studied prospectively for joint disease. Six developed arthralgias while corticosteroid doses were being lowered. Eleven patients (30%) developed knee effusions at a mean interval of 10 days following transplantation. Synovial fluids were colorless or very pale yellow, with few leukocytes (mean, 28/mm3). These benign transudative effusions did not correlate with immunologic abnormalities, transplant rejection, crystal deposition, or avascular necrosis a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

1980
1980
2012
2012

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(1 citation statement)
references
References 20 publications
0
1
0
Order By: Relevance
“…Additionally, idiopathic transudative effusions have been described in a case series of 37 kidney transplant recipients at Indiana University that had 11 cases of arthritis with effusion. Sampling revealed that all effusions were transudative, free of crystals, and had an average WBC count of 28 cells/uL [6]. The differential diagnosis of post-transplant arthralgia is presented in Table 1.…”
Section: Discussionmentioning
confidence: 99%
“…Additionally, idiopathic transudative effusions have been described in a case series of 37 kidney transplant recipients at Indiana University that had 11 cases of arthritis with effusion. Sampling revealed that all effusions were transudative, free of crystals, and had an average WBC count of 28 cells/uL [6]. The differential diagnosis of post-transplant arthralgia is presented in Table 1.…”
Section: Discussionmentioning
confidence: 99%